SCIENTIFIC AND PRACTICAL ASPECTS OF THE DEVELOPMENT OF PROFESSIONAL COMPETENCE OF THE FUTURE TEACHER (Web of Teachers: Inderscience Research, 2025)
The development of professional competence in future teachers is a crucial aspect of teacher education. This article explores the scientific and practical aspects of professional competence, including theoretical foundations, effective methodologies, and practical applications. The study highlights innovative teaching strategies, assessment mechanisms, and the role of technology in enhancing teacher preparation. The findings suggest a multifaceted approach to competency development that integrates theoretical knowledge with practical skills, fostering a well-rounded professional identity.